Correlation of salivary glucose level with blood glucose level in diabetes mellitus: a cross sectional study - Baishya, Reeta; Lahkar, Mangala; Bora, Madhurima; Mazumdar, Arijit (International Journal of Research in Medical Sciences, 2023)
Background: There is alarming rise in number of people with diabetes mellitus over these years. Type 2 diabetes mellitus is the fifth most common condition and the sixth leading cause of mortality amongst the elderly. Finding a relationship between the blood glucose level and its concentration in other body fluids such as the saliva can help in developing an on invasive method for blood sugar assessment replacing venous sampling. Objective of this study was to see the correlation between fasting blood glucose and fasting salivary glucose levels. Methods: This cross sectional study included 200 randomly selected subjects, of which 100 were known diabetes constituted test group and 100 were normal healthy subjects, age- and sex-matched individuals constituted the controls. Fasting blood glucose and salivary glucose levels were measured by using glucose oxidase peroxidase methods. Data were recorded on a preforma in Microsoft excel sheet. Pearson’s coefficient of correlation was applied to find out any significant correlation between the fasting blood glucose and fasting salivary glucose levels. Results: Results were obtained by statistical calculation and plotted with respect to scatter and bar diagram was done and a p<0.05 was considered significant (with 95% CI). Conclusions: A significant positive correlation exists between fasting blood glucose and fasting salivary glucose in both the test groups.